GLOW RADIATOR CO2 - Kubicki, Jan (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The paper presents the physical basis of the constructed model of the fluorescent emitter of CO2 emitting infrared radiation with frequencies exactly coinciding with the absorption spectrum of carbon dioxide. This study describes the basic model and given a physical interpretation of the results. Attention is paid on the properties of the emitted radiation by the device and the ability to use the device in various fields.